Deformational plagiocephaly: the case for an evolutionary mismatch - Renz-Polster, Herbert; Bock, Freia de (Evolution, Medicine, and Public Health, 2018)
Lay Summary: In industrialized societies some babies develop flattening of the back part of their head. It is thought that this comes from sleeping supine, which has been shown to be the safest option for babies. However, this explanation cannot be correct from an evolutionary standpoint: why should safe sleep come at the cost of a misshaped head?Babies in industrialized societies are generally healthy. The medical problems they may be afflicted with are usually well understood. Deformational plagiocephaly presents a notable exception. In many industrialized countries, one in six babies shows posterior flattening of the skull—a feature noteworthy from an evolutionary perspective as the well rounded cranium is part of the ‘Kindchenschema’ evolved to secure care for the infant. It is commonly held that the deformation of the posterior cranium occurs as a consequence of the supine sleep position, now advocated as the safest sleep position for babies by medical experts. This explanation, however, does not fare well in the light of evolutionary theory: why should safe sleep come at the cost of a social handicap? Here, we present an alternative hypothesis that is grounded on evolutionary mismatch theory and exemplifies how evolutionary reasoning can help clarify medical conditions relevant to today’s public health.